2015
DOI: 10.1186/s12943-015-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

OX40 ligand expressed in glioblastoma modulates adaptive immunity depending on the microenvironment: a clue for successful immunotherapy

Abstract: BackgroundGlioblastoma is the most malignant human brain tumor and has a dismal prognosis; however, some patients show long-term survival. The interaction between the costimulatory molecule OX40 and its ligand OX40L generates key signals for T-cell activation. The augmentation of this interaction enhances antitumor immunity. In this present study, we explored whether OX40 signaling is responsible for antitumor adaptive immunity against glioblastoma and also established therapeutic antiglioma vaccination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
(39 reference statements)
1
30
0
Order By: Relevance
“…However, it has been reported that glioma cell lines-derived exosomes lack antigen-presentation and the surface co-modulatory machinery CD80 and CD86 [34] able to cross-react with CD28. It is probable that the presence of other costimulatory molecules such as CD275 (Inducible T-cell co-stimulator ligand, ICOSL) or CD252 (OX40 ligand), which are expressed on glioma cells [38,39], could account for the result that we have observed. A new set of experiments would be required to investigate the implications of this finding, even if this lies outside of the objectives of this work.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been reported that glioma cell lines-derived exosomes lack antigen-presentation and the surface co-modulatory machinery CD80 and CD86 [34] able to cross-react with CD28. It is probable that the presence of other costimulatory molecules such as CD275 (Inducible T-cell co-stimulator ligand, ICOSL) or CD252 (OX40 ligand), which are expressed on glioma cells [38,39], could account for the result that we have observed. A new set of experiments would be required to investigate the implications of this finding, even if this lies outside of the objectives of this work.…”
Section: Discussionmentioning
confidence: 98%
“…One study tested an allogeneic cell‐based vaccine that secreted Fc‐OX40L, Fc‐ICOSL, or Fc‐4‐1BBL versus systemic agonist antibody and found that OX40 was the most effectively targeted pathway . In murine tumor models, OX40 agonist antibody has enhanced survival as a monotherapy or combined with CTLA‐4 blockade . Treatment expanded Tbet hi Eomes hi Granzyme B + CD8 T cells and both Th1 and Th2 CD4 T cells .…”
Section: Targeting Vista In the Context Of Contemporary Antibody Combmentioning
confidence: 99%
“…Increased expression of IL10 and GM-CSF was reported by OX40 triggering in some studies. 21 , 24 It is worth noting that IL10, which is generally considered as a suppressor cytokine, also has antitumor activities. 25-27 …”
Section: Resultsmentioning
confidence: 99%